PENGARUH KONDISI EKONOMI, KONDISI PASAR MODAL DAN KINERJA KEUANGAN TERHADAP RETURN SAHAM - Pradipta, Kadek Agus; Suardana, Ketut Alit (E-Jurnal Akuntansi, 2016)
Stock return is the rate of return expected by an investor when investing in shares in a particular company. Level stock returns are well supported by several factors, including factors of economic conditions, factors of capital market conditions and financial performance . The purpose of this study was to determine the condition of the economy, capital markets and financial performance on stock returns in manufacturing companies in Indonesia Stock Exchange 2011-2013 period. Total sample of companies that are used by 21 companies. Data collected through secondary data. The i analysis technique i used is factor analysis and multiple i linear i regression. Partially, it can be seen that the variable inflation and significant positive effect, IHGS JCI negative and not significant, the Current Ratio variable effect is not significant, effect on Equity Ratio variable positive and significant and variable Eearning per Share positive and significant effect on stock return variables.
Keywords: economic conditions, the condition of the capital markets and financial performance